A new species of the genus Anthaxia (Anthaxia) (Coleoptera: Buprestidae) from The Islamic Republic of Iran - Obořil, Martin; Baňař, Petr G. (Zootaxa, 2017)
Anthaxia (Anthaxia) skorpiki sp. nov., a new species from The Islamic Republic Iran is described and illustrated. The newly described species is compared to the three most similar West Palaearctic members of Anthaxia nitidula species–group, including male genitalia.